Impact of follicular size categories on oocyte quality at trigger day in young and advanced-age patients undergoing GnRH-ant therapy - Yang, Jingwei; Gao, Jing; Wang, Yuting; Liu, Hongya; Lian, Xuemei (Frontiers in Endocrinology, 2023)
Aim To study the effect of follicle sizes of different proportions on oocyte and embryo quality in young and advanced-age patients, provide evidence for personalized protocol adjustment. Methods This was a retrospective study including a total of 11,462 patients who had started their first in vitro fertilization cycle during 2018–2021. We classified patients into groups according to the size of the dominant proportion of follicles on the human chorionic gonadotropin trigger day: Large, Medium, Small, and Equal (containing equivalent proportions of all three size categories). The Cochran–Mantel–Haenszel test was used to compare factors such as the metaphase II oocyte rate, normal fertilization rate, and two pronuclei cleavage rate between groups. General linear model analysis was performed for inter-group comparison of the oocyte and embryo quality. Results In patients < 35 years, the GLM demonstrated that the Large and Medium groups had positively impacted on the development of MII oocyte and live birth rate(LBR) of first embryo transfer(ET)(β>0, all P value < 0.05);and had less likely to develop into unavailable oocyte, degenerated oocyte, GV oocyte and MI oocyte rates relative to the Small group( β<0, all P value < 0.05). And among patients ≥ 35 years, the Medium group had positively impacted on the development of MII oocyte and 2PN rates relative to the Small group(β>0, all P value < 0.05); and had less likely to develop into MI oocytes relative to the Small group( β<0, all P value < 0.05). The GLM indicated that AMH, along with Gn total dose, start dose, and Gn days, had significant impact on oocyte and embryo quality. For young patients, age was not a significant influencing factor, but for advanced-age patients, age influenced the outcomes. Conclusion Our analysis suggests that for young patients (< 35 years), triggering when there is a high proportion of large or medium follicles results in better quality oocytes, while for older patients (≥ 35 years), it is better to trigger when the proportion of medium follicles is no less than that of small follicles. Further research is required to confirm these findings.